OLIY TA’LIMDA GEOGRAFIYA FANIDA XORIJIY TAJRIBALARDAN FOYDALANISh USULLARI - Gaypova, R.; Abdurahmanov, S.T.; Sapaeva, M.M. (SCIENCE and SOCIETY, 2025)
This article analyzes the issues of using foreign advanced experiments in teaching geography in the higher education system of Uzbekistan on a scientific basis. The study explores specific aspects of geography education in the higher education systems of the United States, Finland, Germany, South Korea and Turkey. Also, the advantages, problems and prospects of integrating foreign approaches into the national education system in Uzbekistan higher educational institutions are shown. The article analyzes advanced techniques such as innovative pedagogy, digital technologies (GIS systems), student-centered education and academic mobility, and covers the mechanisms of their application in Uzbekistan. As a result, it has been proven that the adaptation of foreign experiences to local conditions serves to improve the quality of geography and prepare competitive personnel.
Keywords: geography education; foreign experience; innovative methods; GIS technologies; student-centered teaching; academic mobility; higher education; Integration; Digital Geography; pedagogical innovations